Pendekatan Integratif Untuk Merancang Kurikulum Merdeka Berbasis Deep Learning dalam Mata Pelajaran Ekonomi di SMA N 1 Boyolali - Nida Balqis Nabila; Rasyida Septi Arnetta; Bibit Setyowati (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
The research intends to formulate an integrative approach for designing the Merdeka Curriculum based on Deep Learning in the Economics subject at SMA N 1 Boyolali. The rapid advancement of digital technology demands more adaptive, contextual, and student-centered learning models aligned with 21st- century competencies. Using a an exploratory research approach supported by a structured assessment of prior studies (SLR), this research synthesizes theoretical perspectives and previous studies related to curriculum design, deep learning, and educational innovation. The results reveal that the incorporation of Deep Learning into the Merdeka Curriculum offers a more responsive and data-driven framework, enabling deeper conceptual understanding, critical thinking, and problem-solving skills in Economics learning. However, several challenges were identified, including teachers limited digital competence, insufficient infrastructure, and minimal curriculum innovation training. The study emphasizes the significance of combining technological and pedagogical innovation to strengthen learning quality. The results provide a conceptual model that educators can adopt to design an adaptive curriculum aligned with students’ characteristics and contemporary educational demands.